2010
DOI: 10.1590/s1413-35552010000100007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different supermarket checkout workstations on trunk kinematics of checkout operators

Abstract: Objectives: This study analyzed the effect of a standard and a modified checkout workstation during a simulated task on trunk postures of a supermarket checkout operator. Methods: Eight participants performed a task involving grasping, scanning and depositing products, while 3D images of the trunk were collected. Results: A number of kinematic changes were observed in trunk posture. A greater anterior flexion (3.0±1.2 o ) and lateral bending during grasping (7.1±1.4 o ) were found in the standard checkout work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
(28 reference statements)
2
21
0
Order By: Relevance
“…[110][111][112][113][114][115] Uncomfortable workstation design is one problem experienced by cashiers that needs to be evaluated and improved. 107,114,[116][117][118] To perform the checking out task it is necessary to scan the UPC printed on items to automatically identify them. While advancements in scanning technology would be expected to have a fruitful impact on scanning performance and behavior, this impact can be limited by package design, and quality and proper placement of the UPC.…”
Section: Cashier Checkoutmentioning
confidence: 99%
See 1 more Smart Citation
“…[110][111][112][113][114][115] Uncomfortable workstation design is one problem experienced by cashiers that needs to be evaluated and improved. 107,114,[116][117][118] To perform the checking out task it is necessary to scan the UPC printed on items to automatically identify them. While advancements in scanning technology would be expected to have a fruitful impact on scanning performance and behavior, this impact can be limited by package design, and quality and proper placement of the UPC.…”
Section: Cashier Checkoutmentioning
confidence: 99%
“…Rodacki and Vieira, 107 Shinnar et al, 114 Carrasco et al, 116 Spielholz et al, 117 and Draicchio et al 118 Workstation design may not be comfortable; design interventions were approved to improve the checking out process. UPC location and scanning Kihlstedt and Hägg, 111 Madigan and Lehman, 115 Hoffman, 119,121 and Madigan 120 Packaging design and UPC placement can limit the usability of scanning technologies.…”
Section: Improving Cashiers' Performancementioning
confidence: 99%
“…Rodacki & Vieira (2010) found that the average time experience as a checkout operator is 10.1 ± 2.6 months. Liedke (2001) reports that trade is not as demanding in a matter of past experience, which proves the fact that research presented years of low experience.…”
Section: Professional Research Questionnaire Checkout Operatormentioning
confidence: 99%
“…Investigators have previously reported the consequence of repeated movements [17] and lifting on checkout operators [18]. The risk of injury through manoeuvring a shopping trolley has also been explored, with shoppers susceptible to pain and stiffness in the neck, shoulders, the upper and lower extremities as well as the lumbar spine [19].…”
Section: Introductionmentioning
confidence: 99%